Tourism as a multilevel discipline: between global interdependences and local aspirations (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The tourism Sector presents a fragmented nature which requires different levels of governments and regulations. The main purpose of this study is to describe tourism law at the international, national and regional level. The COVID-19 crisis has affected tourism with unprecedent economic impactshad an unprecedented economic impact on tourism. Economic funds in thefrom Next Generation EU generation Next are represent the first steps for the recovery, but the urge is to solve some institutional problems related to the Italian devolutive process.
Keywords: Tourism; Multilevel regulation; COVID-19; Cooperation